Reflection and Quality Assessment in Service-Learning Projects. When, With Whom, and Why - Lorenzo Moledo, María del Mar; Sáez-Gambín, Daniel; Ferraces Otero, María José; Varela Portela, Cristina (Frontiers in Education, 2021)
Among all the elements likely to be considered criteria that determine the quality of a service-learning (SL) project, the scientific literature points to reflection. This work is aimed at analyzing the influence of reflection on certain variables that mediate the educational performance of university students, as well as their satisfaction with the acquired knowledge. More specifically, what interested us was to analyze how this reflective process should be, thus we defined three independent variables: the time at which it is performed, the actors involved, and its objectives. The sample was made up of 295 students from the University of Santiago de Compostela, who were participating in SL projects that had been developed in different degree programs. Three instruments were used for data collection, two aimed at the students and one at the teaching staff responsible for the project. The main conclusion, given the results, is that reflection must be carried out from the beginning to the end of the project or, failing this, only at the end. Secondly, priority should be given to involving all the actors concerned, paying particular attention at least to the work group. Finally, it must be oriented both toward sharing feelings about the experience, relating the service to the contents of the subject, and developing attitudes and values. In this way, the status of reflection as one of the key factors in the development of quality experiences in SL is confirmed, showing that those that present a more rigorous and structured reflection have a greater impact on the variables mediating performance and on the students’ satisfaction with their learning.